Conformal compensators and manifest type IIB S-duality - Berkovits, Nathan [UNESP] (My University, 1998)
Using the conformal compensator superfields of N = 2 D = 4 supergravity, the Type IIB S-duality transformations are expressed as a linear rotation which mixes the compensator and matter superfields. The classical superspace action for D = 4 compactifications of Type IIB supergravity is manifestly invariant under this transformation. Furthermore, the introduction of conformal compensators allows a Fradkin-Tseytlin term to be added to the manifestly SL(2,Z)-covariant sigma model action of Townsend and Cederwall. © 1998 Published by Elsevier Science B.V.